Identification Of Sports Injuries In Football Players - Syahruddin Syahruddin; Muh. Sahib Saleh; Muhammad Syahrul Saleh (Universitas Singaperbangsa Karawang, 2024)
This research is a descriptive study with a survey method. This study aims to determine the body parts and types of injuries that often occur in BKMF FIKK UNM Football Players with a sample size of 30 people with sampling using saturated sampling techniques where saturated sampling is a sampling technique when all members of the population are used as samples. The data collection technique in this study was by giving questionnaires to several respondents and the respondents filled out the questionnaires, after which the questionnaires were returned to the researcher. From the results of the descriptive analysis, it can be seen that injuries to the dominant body parts that occur in BKMF FIKK UNM Football Players are the legs and feet with a percentage of 53.11%, then the arms and hands by 27.55%, the head 8.87%, the spine by 6.09%, and the body by 4.37%. The most dominant types of injuries that occur in BKMF FIKK UNM Football Players are bruises 27.54%, then sprains/strains 21.39%, fractures 17.51%, dislocations 13.90%, abrasions 10.70%, cramps 6.68%, and head injuries (fainting) as the type of injury that is least experienced, namely 2.27%.